THE EFFECT OF PROMPTING ON IMPROVING SELF-CARE ABILITY IN GRADE IX MENTALLY DISABLED STUDENTS AT KARANGANYAR STATE SLB - Christina Wahyu Putri; Tias Martika; Mahardika Supratiwi (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2024)
This study aims to determine the effect of prompting on the improvement of self-care abilities in ninth-grade students with intellectual disabilities at SLB Negeri Karanganyar. This research is an experimental quantitative study with a Single Subject Research (SSR) design using A-B-A. The subject of this research is a ninth-grade student with intellectual disabilities. The sampling technique used is a nonprobability sampling technique, specifically purposive sampling. The data collection technique used was a performance test. The reliability test technique uses interrater reliability with a reliability of 0.999. The data analysis technique in this study uses descriptive statistics and visual graph analysis, which includes within-condition analysis and between-condition analysis. Based on the research results, at the baseline 1 stage (A1), the subjects' abilities were still in the low category with a mean score of 49.53. At the intervention stage (B), the subjects' abilities showed improvement, evidenced by a mean score of 73.60. At the baseline 2 stage (A2), the subjects' abilities continued to improve with a mean score of 98.14. The research results show that the provision of prompting has an impact on the improvement of self-care abilities in ninth-grade students with intellectual disabilities at SLB Negeri Karanganyar.